Exploring Technological, Safety and Probiotic Properties of Enterococcus Strains: Impact on Rheological Parameters in Fermented Milk - Souraya Sakoui; Reda Derdak; Oana Lelia Pop; Dan Cristian Vodnar; Fatimazahra Jouga; Bernadette-Emőke Teleky; Boutaina Addoum; Elemér Simon; Ramona Suharoschi; Abdelaziz Soukri; Bouchra El Khalfi (Foods, 2024)
Enterococci, known for their resilience, are commonly found in food, the environment, and the gastrointestinal tracts of humans and animals. In recent research, six strains of enterococcus were isolated from bat guano. These include Enterococcus mundtii SRBG1, Enterococcus gallinarum SRBG3, Enterococcus faecium SRBG2, Enterococcus casseliflavus EC1, and Enterococcus devriesei CAU 1344. Identification was done using 16S DNA analysis. Each strain underwent evaluation for its technological properties (such as tolerances to various NaCl concentrations and temperatures, as well as amylolytic, β-galactosidase, lipolytic, and proteolytic activities, and EPS production) and selected probiotic properties (including safety profile, resistance to 0.3 percent bile salts and gastric juice with a pH of 2.5, lysozyme tolerance, and antibacterial and antibiofilm activities against four foodborne pathogens). The results were analyzed using Principal Component Analysis. This analysis revealed that E. mundtii SRBG1 and E. gallinarum SRBG3, followed by E. faecium SRBG2, were most closely associated with a broad range of technological characteristics and were subsequently used for fermenting skimmed milk. The rheological properties of the samples indicated a shear-thinning or non-Newtonian behavior. Furthermore, during storage of the fermented milk at 4 °C over periods of 1, 7, 14, and 21 days, there were no significant changes in bacterial count (at around 7 log10 CFU/mL) and pH when fermented with the three evaluated strains.